Variación diacrónica del léxico disponible de una comunidad bilingüe - Serrano Zapata, Maribel (Studia Romanica Posnaniensia, 2025)
In this paper we analyze lexical variation in the diachronic axis based on the data offered by lexical availability. To do this, we compared two samples of 120 pre-university students from the city of Lleida taken at different times (2003-2023). The data with respect to the two languages of the community, Spanish and Catalan, and in relation to two centers of interest (The Human Body and Games and Distractions) reveal a loss in the production of available lexicon that is accentuated in the case of the Catalan language. The two lexical fields show a contrary behavior in the period analyzed: while the vocabulary of The Human Body shows great stability, changes in the forms of youth leisure cause a great variability in Games and Distractions. The two languages follow similar patterns of diachronic evolution.